Not all benign: disease course, complications, and sequalae of chronic recurrent multifocal osteomyelitis in children. Issue 5 (5th September 2022) - Yasin, Shima; Sato, T. Shawn; Ferguson, Polly
Abstract : Purpose of review: Advances in pathogenesis of chronic recurrent multifocal osteomyelitis in children (CRMO) have shaped therapeutic strategies. The use of whole-body MRI (WBMRI) and improved awareness of CRMO has increased rates and timeliness of CRMO diagnoses. In this review, we highlight the findings from recently published CRMO cohorts and describe the course, complications, and long-term sequalae of CRMO. It is important for clinicians to be aware of the potential for long-term sequelae in order to optimize therapy and avoid complications. Recent findings: Despite recent advances in defining disease pathogenesis, children with CRMO continue to suffer from complications and deformities. Involvement of the spine can be asymptomatic and is not as rare as previously suggested. This can result in damaging outcomes, such as vertebral fractures and permanent deformities. A subset of patients has polycyclic disease course and some continue to have active disease for years and well into adulthood, with significant impacts on quality of life. Summary: These recent findings have considerable implication on clinical practice regarding diagnosis, treatment, and monitoring of the disease. Collectively, they support the need for continued monitoring of the disease and screening using comprehensive imaging, such as WBMRI.